Impact of a bundle of care (intravenous iron, erythropoietin and transfusion metabolic adjustment) on post-operative transfusion incidence in cardiac surgery: a single-centre, randomised, open-label, parallel-group controlled pilot trialResearch in context - Marine Saour; Cinderella Blin; Norddine Zeroual; Marc Mourad; Maïlis Amico; Philippe Gaudard; Marie-Christine Picot; Pascal H. Colson (Elsevier, 2024)
Summary: Background: Red blood cell (RBC) transfusions are frequent in patients after cardiac surgery. This study assessed whether a bundle of care including pre-operative and post-operative administration of erythropoietin (EPO) with intravenous iron supplementation, and restrictive transfusion adjusted for ScvO2 could result in reduced postoperative transfusions. Methods: In this single-centre, randomised, open-label, parallel-group controlled pilot study, patients undergoing elective cardiac surgery with high risk of transfusion in a University Hospital were enrolled by the investigator and the randomisation procedure using a central internet-based system was made by the clinical research assistant. Since the trial was open-label, no masking was used. Patients were assigned (1:1) to either the STOP group (40,000 IU subcutaneous EPO combined with 20 mg/kg intravenous ferric carboxymaltose if Hb < 13 g/dL the day before surgery or at ICU admission, and RBC transfusion if Hb ≤ 8 g/dL and ScvO2 ≤ 65%, or additional EPO dose if 8 < Hb < 13 g/dL) or to the control group (RBC transfusion if Hb ≤ 8 g/dL, or, if 8 < Hb < 13 g/dL, intravenous iron sucrose 200 mg or 300 mg according to weight). Primary outcome was the incidence of postoperative RBC transfusion up to hospital discharge or postoperative day 28. The trial is registered with ClinicalTrials.gov, NCT04141631. Findings: Between Jan 20, 2020, and Sept 6, 2022, among 128 patients enrolled, 123 (male, 54.4%, 67/123) were included in the full analysis set: 62 in the STOP group and 61 in the control group. Nine patients (14.5%, 9/62) in the STOP group required RBC transfusion vs 19 (31.2%, 19/61) in the control group (odds ratio 0.37 [95% CI: 0.15-0.91], p = 0.03). The median length of follow up to transfusion was 2.6 days (1.5; 4.6) and 3.3 (1.6; 4.2) in control and STOP groups respectively (p = 0.61). Interpretation: The bundle of care may reduce postoperative RBC transfusion. The findings should be taken with caution due to the unblinded and exploratory nature of the study. Funding: University of Montpellier Hospital and Vifor Pharma.